PELATIHAN INOVASI PEMBELAJARAN PROJECT BASED LEARNING UNTUK PENINGKATAN KECAKAPAN ABAD 21 MELALUI SINEMATOGRAFI - Umi Salamah; Mukarom; Indrawati Pusparini; Hanifitria Ningrum (Kreativitas Pada Pengabdian Masyarakat (Krepa), 2024)
This training aims to provide understanding and skills to applying project-based learning (PjBL) innovations to improve 21st Century competencies through cinematography in an effective and entertaining way. The training was attended by 28 teachers in the multimedia room of SMAN 1 Garum. The training and mentoring method has three stages, such as presentation using power point media, video tutorials, and product examples; practice and assistance in making products; and uploading products. The results of this training and mentoring were that all participants were able to complete and upload the training products with enthusiasm, effectiveness, and fun. It is recommended that the training and mentoring methods applied by the presenters can be obtained by the participants in applying PjBL to students.